P-doped C3N4-BiOCl0. 7I0. 3 heterojunction photocatalyst as well as preparation method and application thereof
By constructing a heterojunction photocatalyst with P-doped C3N4 and BiOCl0.7I0.3, the problem of poor removal of micro pollutants by existing water treatment methods is solved, and efficient degradation of pollutants such as Cr(VI), tetracycline hydrochloride and rhodamine B is achieved, and good cycle stability is achieved.
Patent Information
- Application Number
- CN202510038355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing water treatment methods have poor removal of tiny particles or soluble pollutants, and may cause secondary contamination after use of conventional chemical oxidants, which are complex in operation and high in cost.
PCN was prepared by thermal condensation method using P-doped C3N4 and BiOCl0.7I0.3 heterojunction photocatalyst, and BOCI nanosheets were synthesized by hydrothermal method to construct a 2D/2D van der Waals heterojunction to improve the photocatalytic activity of the photocatalyst.
It has achieved efficient degradation of pollutants such as Cr(VI), tetracycline hydrochloride and rhodamine B, showing photocatalytic activity better than traditional bismuth-based photocatalysts and C3N4, and has good cycling stability.
Smart Images

Figure CN119819348A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, and in particular to a 2D / 2D P-doped C3N4-BiOCl 0.7 I 0.3 Preparation method and application of heterojunction photocatalyst. Background Art
[0002] With the rapid development of urbanization and the progress of industrial and agricultural production, the pollution problem in water bodies has become increasingly prominent. The water environment is affected by a variety of pollutants, including phenols, aromatic hydrocarbons, polycyclic aromatic hydrocarbons, antibiotics, organic pesticides, disinfection by-products and perfluorinated compounds, heavy metal ions, dyes, etc. These trace pollutants may have a negative impact on the health of humans and other animals even at extremely low concentrations, including damage to reproduction, development, nerves and the immune system, and may even cause cancer, teratogenesis and cause gene mutations in humans or animals.
[0003] Conventional water treatment methods are usually divided into physical methods, biological methods and chemical methods. The physical treatment method is to separate the organic matter in the wastewater by physical action, and then carry out subsequent treatment, such as membrane separation method and physical adsorption method. The physical treatment method is simple to operate and does not pollute the environment, but the removal effect of tiny particles or soluble pollutants is poor, and it cannot completely remove organic matter. Biological treatment is a method of eliminating micropollutants by culturing microorganisms and applying microbial oxidation and decomposition, but it is only effective for certain specific micropollutants and is greatly affected by environmental factors. At the same time, the treatment efficiency is limited by factors such as temperature and pH value, and the treatment cycle is long. Chemical treatment usually adds chemical oxidants to wastewater to remove organic matter in wastewater through chemical reactions, which can improve the biodegradability of organic wastewater. However, this method requires a large amount of chemical agents, which may cause secondary pollution, and the operation is complicated and costly. When using some chemical oxidants, such as sodium hypochlorite (NaClO), carcinogenic disinfection byproducts will be produced.
[0004] In recent years, semiconductor photocatalytic technology has stood out from many environmental pollution treatment technologies due to its green, environmentally friendly, energy-saving and high-efficiency characteristics. Designing and synthesizing efficient and stable photocatalysts is the key to achieving efficient photocatalytic degradation of pollutants. Due to the limitations of the physical properties of semiconductors themselves, the strong light absorption ability of a single semiconductor often means low photogenerated carrier separation efficiency, thus limiting its photocatalytic effect. To improve the photocatalytic effect of the catalyst, it is necessary to regulate the separation of its photogenerated carriers. Summary of the invention
[0005] In view of this, the present invention aims to provide a P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst and its preparation method and application.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is a P-doped C3N4 and BiOCl 0.7 I 0.3 The preparation method of the heterojunction photocatalyst comprises the following steps:
[0008] After dissolving melamine and ammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN;
[0009] After Bi(NO3)3, KCl and KI are uniformly dispersed in solvent 2, the pH is adjusted and then a hydrothermal reaction is performed to obtain BOCI nanosheets;
[0010] The PCN and BOCI nanosheets are uniformly dispersed in solvent 3 and dried until solvent 3 is completely removed to obtain the P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalysts.
[0011] The second technical solution of the present invention is a P-doped C3N4 and BiOCl prepared by the above preparation method. 0.7 I 0.3 Heterojunction photocatalysts.
[0012] The third technical solution of the present invention is a method of doping C3N4 and BiOCl 0.7 I 0.3 Application of heterojunction photocatalyst in photocatalytic degradation of pollutants; the pollutants are Cr(VI), tetracycline hydrochloride or rhodamine B.
[0013] The present invention discloses the following technical effects:
[0014] The preparation process of the present invention is simple. PCN is composite-modified by BOCI, and a direct Z-type van der Waals heterojunction photocatalyst is successfully constructed for efficient degradation of common organic pollutants. Van der Waals heterojunction is a special semiconductor structure formed by combining two different types of semiconductor materials through van der Waals forces. The formation of this heterojunction depends on the van der Waals force between the two materials, and does not need to be achieved through lattice matching, so the materials can be spliced like building blocks.
[0015] The construction of heterojunction significantly improves the performance of the catalyst. The P-doped C3N4 and BiOCl prepared by the present invention 0.7 I 0.3The heterojunction photocatalyst exhibits superior photocatalytic activity to traditional bismuth-based photocatalysts and C3N4. The construction of the heterojunction promotes the separation of photogenerated carriers, and the increased specific surface area provides more active sites for the reaction. The Z-type charge transfer mechanism promotes carrier separation while providing stronger reduction ability, showing excellent photocatalytic effects.
[0016] The photocatalyst of the present invention has universal applicability and good cycle stability for pollutant degradation, and has high degradation efficiency for Cr(VI), tetracycline hydrochloride and rhodamine B. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 P-doped C3N4 and BiOCl prepared in Example 1 0.7 I 0.3 TEM image of heterojunction photocatalyst at 100nm scale;
[0019] Figure 2 P-doped C3N4 and BiOCl prepared in Example 1 0.7 I 0.3 HRTEM image of the heterojunction photocatalyst (a) and TEM image at 5 nm scale (b);
[0020] Figure 3 P-doped C3N4 and BiOCl prepared in Example 1 and Example 4-7 0.7 I 0.3 XRD pattern of heterojunction photocatalyst;
[0021] Figure 4 P doped C3N4 and BiOCl in the present invention 0.7 I 0.3 Optical absorption and energy band position analysis diagram of heterojunction photocatalysts, where (a) is the UV-visible diffuse reflectance spectra of different catalysts, (b) is the Tauc-plot of PCN and BOCI, (c) is the VB-XPS spectra of PCN and BOCI, and (d) is the Mott-Schottky curves of PCN and BOCI;
[0022] Figure 5 P-doped C3N4 and BiOCl in Example 1 0.7 I 0.3Degradation effect diagram of heterojunction photocatalyst used for degradation of Cr(VI), tetracycline hydrochloride and rhodamine B. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] C3N4 is a unique graphene-like layered material with a suitable energy band structure and sheet-like stacking morphology, and has great application potential in the field of photocatalysis. Therefore, the present invention takes the C3N4-based photocatalyst with excellent performance as the research object, and adjusts the separation efficiency of its photogenerated carriers by doping and constructing a heterojunction.
[0029] Although heteroatom modification can effectively improve the photocatalytic activity of the catalyst, in order to meet the increasing demand for catalyst performance, the catalytic effect can be further improved by further modification combined with other effective photocatalytic modification strategies. Therefore, the present invention prepares the precursor PCN by thermal condensation method, and synthesizes the solid solution BiOCl of bismuth iodide and bismuth chlorine with suitable band structure and morphology by hydrothermal method. 0.7 I 0.3 (BOCI) nanosheets successfully constructed a 2D / 2DP-doped C3N4 and iodine-chloride-bismuth-oxygen Z-type van der Waals heterojunction by simple mixing. The large specific surface area of the 2D / 2D layered stacking structure provides more surface active sites. At the same time, the large-scale continuous stacking structure forms a strong electronic coupling effect, thereby reducing the impedance of carrier migration at the interface. The construction of the heterojunction of the present invention broadens the light absorption range of the material, thanks to the enhanced carrier separation efficiency and strong redox ability of its Z-type charge transfer mechanism. The heterojunction of the present invention exhibits good photocatalytic performance in degrading tetracycline hydrochloride and Cr(VI) under visible light. The best performing heterojunction sample has a photocatalytic degradation performance of Cr(VI) that is 20 times that of nanosheet C3N4, showing universality and good cycle stability for pollutant degradation.
[0030] The first aspect of the present invention provides a P-doped C3N4 and BiOCl 0.7 I 0.3 The preparation method of the heterojunction photocatalyst comprises the following steps:
[0031] After dissolving melamine and diammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN (i.e., P-doped C3N4 photocatalyst);
[0032] After Bi(NO3)3, KCl and KI are uniformly dispersed in solvent 2, the pH is adjusted and then a hydrothermal reaction is performed to obtain BOCI nanosheets;
[0033] The PCN and BOCI nanosheets are uniformly dispersed in solvent 3 and dried until solvent 3 is completely removed to obtain the P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalysts.
[0034] In some embodiments of the present invention, the solvent 1 is water; the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.1% to 3%.
[0035] In some embodiments of the present invention, the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.5%.
[0036] The present invention does not specifically limit the amount of solvent 1, as long as it can completely dissolve melamine and diammonium phosphate. The present invention does not specifically limit the drying method, temperature and time, as long as the solvent 1 can be completely removed, for example: drying in a water bath at 80°C until the solvent 1 is completely removed.
[0037] In some embodiments of the present invention, the two thermal condensation reactions are specifically: first, the temperature is raised to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 2-3 hours. After the temperature is kept, it is cooled to room temperature, the reaction product is ground, and then the ground powder is heated to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 3-4 hours. The present invention regulates the morphology of PCN through two thermal condensation treatments, so that it is peeled into nanosheets.
[0038] The reason why the present invention limits the parameters of the two thermal condensations to the above range is that the heating rate is a key factor in the performance of the synthesized C3N4 material. A slower heating rate helps to achieve a higher degree of nitridation, uniform particle size, higher crystallinity and less carbon residue, thereby obtaining C3N4 with higher purity and better performance. Although rapid heating can shorten the reaction time, it may lead to problems such as incomplete nitridation, excessive carbon residue, uneven particles, disordered structure, etc., affecting the performance of the final material.
[0039] In some embodiments of the present invention, the solvent 2 is water; the pH is 6; the mass ratio of Bi(NO3)3, KCl and KI is 395:52:49. The present invention does not specifically limit the amount of solvent 2, as long as it can evenly disperse Bi(NO3)3, KCl and KI. The present invention does not specifically limit the dispersion method, and conventional technical means of those skilled in the art can be used, such as ultrasonic dispersion.
[0040] In the process of synthesizing bismuth oxyhalides, BiOCl with adjustable visible light responsive band structure can be synthesized by controlling the type and ratio of the added halogen. x Br 1-x 、BiOCl x I 1-x and BiOBr x I 1-x Solid solution, among which only solid solution BiOCl 0.7 I 0.3 (BOCI) has a suitable band structure and can form a Z-type heterojunction with PCN.
[0041] In the present invention, when the mass ratio of Bi(NO3)3 is too high or too low, the generation of BOCl and BOI will be inhibited. As the proportion of KCl increases, the band gap of the synthesized BOCI solid solution gradually increases, the redox ability is enhanced, and the light absorption ability is reduced. When the proportion of KI increases, the band gap of the synthesized BOCI solid solution gradually decreases, the redox ability is reduced, the light absorption ability is increased, and the recombination of photogenerated carriers increases.
[0042] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 150-160° C., and the time is 20-26 hours.
[0043] In the hydrothermal synthesis of iodine chlorine bismuth oxide catalyst process, temperature and reaction time jointly determine the crystal structure, physical phase, particle size, specific surface area and catalytic performance of the catalyst. Higher temperature helps to improve the crystallinity and catalytic activity of the crystal, but too high a temperature may cause excessive crystal growth or phase change, affecting catalytic performance. Too short a reaction time may cause the crystal to be incomplete and the catalytic activity to be lower, while too long a reaction time may cause the crystal size to be too large and the specific surface area to be reduced, thereby affecting catalytic performance. Therefore, the present invention limits the parameter of hydrothermal reaction to the above range. Usually the optimum reaction time is 12-36 hours.
[0044] In some embodiments of the present invention, after the hydrothermal reaction is completed, washing and drying steps are further included. The present invention does not specifically limit the washing and drying methods, and conventional technical means of those skilled in the art can be used, for example: washing with deionized water and ethanol in sequence, and drying at 80°C for 12 hours.
[0045] In some embodiments of the present invention, the solvent 3 is ethanol; the mass ratio of the PCN to the BOCI nanosheet is 9:1 to 5:5. The present invention does not specifically limit the amount of solvent 3, as long as it can evenly disperse the PCN and BOCI nanosheets. The present invention does not specifically limit the dispersion method, and conventional technical means of those skilled in the art can be used, for example: ultrasonic treatment followed by stirring treatment.
[0046] In an ideal composite heterojunction, an effective heterojunction should be formed between BOCI and PCN to promote the migration of electrons from PCN to BOCI, thereby inhibiting the recombination of electron-hole pairs and improving the efficiency of the photocatalytic reaction. When the mass ratio of PCN to BOCI is too high, agglomeration may form between the same components, the specific surface area is reduced, the active sites are reduced, and the effective interface contact area is reduced, which affects the diffusion and migration of photogenerated carriers at the interface. The present invention balances the photocatalytic performance, electronic conduction performance and stability of the two by limiting the mass ratio of PCN and BOCI nanosheets to the above parameter range, thereby ensuring the high efficiency of the composite heterojunction.
[0047] The second aspect of the present invention provides a P-doped C3N4 and BiOCl prepared by the above preparation method. 0.7 I 0.3 Heterojunction photocatalysts.
[0048] The third aspect of the present invention provides a P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst. Application in photocatalytic degradation of pollutants; the pollutants are Cr(VI), tetracycline hydrochloride or rhodamine B.
[0049] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0050] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0051] Example 1
[0052] A P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst, the preparation steps are as follows:
[0053] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain PCN:
[0054] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a P:C3N4 molar ratio of 0.5%), dissolve them in 60 mL of distilled water in a beaker, dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed, then dry them in an oven at 80°C for 12 h, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 2 h. After natural cooling, take them out and grind them into powder to obtain block C3N4.
[0055] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 4h. The obtained sample was 0.5% PCN.
[0056] Step 2, obtain BOCI nanosheets by hydrothermal method:
[0057] 1) Add 1.580g Bi(NO3)3, 0.208g KCl and 0.199g KI to 60mL deionized water, and adjust the pH to 6 with sodium hydroxide solution after ultrasonic dispersion. Continue stirring for 30min, then transfer the mixture solution to a 100mL polytetrafluoroethylene autoclave and place it in an oven for hydrothermal reaction at 160℃ for 24h. After cooling to room temperature, collect the crude sample, wash with deionized water and ethanol, dry at 80℃ for 12h, and grind to obtain orange-yellow BiOCl 0.7 I 0.3 , which is BOCI nanosheet.
[0058] Step 3, compound PCN and BOCI nanosheets by simple mixing method:
[0059] Weigh 0.6 g 0.5% PCN and 0.4 g BOCI nanosheets, add them into a beaker containing 40 mL ethanol, ultrasonicate them at 60 kHz for 30 min, stir them for 5.5 h, dry the water in a water bath at 80 °C, collect the catalyst, and dry it again to obtain P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst (denoted as 6:40.5% PCN / BOCI).
[0060] Example 2
[0061] A P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst, the preparation steps are as follows:
[0062] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain precursor PCN:
[0063] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a P:C3N4 molar ratio of 0.1%), dissolve them in 60 mL of distilled water in a beaker, dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed, then dry them in an oven at 80°C for 12 h, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 4°C / min, a target temperature of 540°C, and a holding time of 3 h. After natural cooling, take them out and grind them into powder to obtain block C3N4.
[0064] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 4°C / min, a target temperature of 540°C, and a holding time of 3h. The obtained sample was 0.1% PCN.
[0065] Step 2, using a hydrothermal method to obtain the precursor BOCI nanosheets:
[0066] 1.580g Bi(NO3)3, 0.208g KCl and 0.199g KI were added to 60mL deionized water, and after ultrasonic dispersion, the pH was adjusted to 6 with sodium hydroxide solution, and stirring was continued for 30min. Then, the mixture solution was transferred to a 100mL polytetrafluoroethylene autoclave and placed in an oven for hydrothermal reaction at 150℃ for 24h. After cooling to room temperature, the crude sample was collected, washed with deionized water and ethanol, dried at 80℃ for 12h, and ground to obtain orange-yellow BiOCl 0.7 I 0.3 , which is BOCI nanosheet.
[0067] Step 3, compound PCN and BOCI nanosheets by simple mixing method:
[0068] Weigh 0.6g 0.1% PCN and 0.4g BOCI nanosheets, add them to a beaker containing 40mL ethanol, ultrasonicate them at 50KHz for 1h, stir for 4h, dry the water in a water bath at 80℃, collect the catalyst, and dry it again. 0.7 I 0.3 Heterojunction photocatalyst (denoted as 6:40.1% PCN / BOCI).
[0069] Example 3
[0070] A P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst, the preparation steps are as follows:
[0071] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain precursor PCN:
[0072] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a 3% P:C3N4 molar ratio), dissolve them in 60 mL of distilled water in a beaker, dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed, then dry them in an oven at 80°C for 12 h, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 6°C / min, a target temperature of 560°C, and a holding time of 3 h. After natural cooling, take them out and grind them into powder to obtain block C3N4.
[0073] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 6°C / min, a target temperature of 560°C, and a holding time of 3h. The obtained sample was 3% PCN.
[0074] Step 2, using a hydrothermal method to obtain the precursor BOCI nanosheets:
[0075] 1) 1.580g Bi(NO3)3, 0.208g KCl and 0.199g KI were added to 60mL deionized water, and after ultrasonic dispersion, the pH was adjusted to 6 with sodium hydroxide solution, and stirring was continued for 30min. Then, the mixture solution was transferred to a 100mL polytetrafluoroethylene autoclave and placed in an oven for hydrothermal reaction at 160℃ for 20h. After cooling to room temperature, the crude sample was collected, washed with deionized water and ethanol, dried at 80℃ for 12h, and ground to obtain orange-yellow BiOCl 0.7 I 0.3 , which is BOCI nanosheet.
[0076] Step 3, compound PCN and BOCI nanosheets by simple mixing method:
[0077] Weigh 0.6g 3% PCN and 0.4g BOCI nanosheets, add them to a beaker containing 40mL ethanol, ultrasonicate them at 50KHz for 2h, stir them for 12h, dry the water in a water bath at 80℃, collect the catalyst, and dry it again. 0.7 I 0.3 Heterojunction photocatalyst (denoted as 6:43% PCN / BOCI).
[0078] Example 4
[0079] A P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst, the preparation steps are as follows:
[0080] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain precursor PCN:
[0081] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a P:C3N4 molar ratio of 0.5%), dissolve them in 60 mL of distilled water in a beaker, dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed, then dry them in an oven at 80°C for 12 h, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 2 h. After natural cooling, take them out and grind them into powder to obtain block C3N4.
[0082] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 4h. The obtained sample was 0.5% PCN.
[0083] Step 2, obtain BOCI nanosheets by hydrothermal method:
[0084] 1) Add 1.580g Bi(NO3)3, 0.208g KCl and 0.199g KI to 60mL deionized water, and adjust the pH to 6 with sodium hydroxide solution after ultrasonic dispersion. Continue stirring for 30min, then transfer the mixture solution to a 100mL polytetrafluoroethylene autoclave and place it in an oven for hydrothermal reaction at 160℃ for 24h. After cooling to room temperature, collect the crude sample, wash with deionized water and ethanol, dry at 80℃ for 12h, and grind to obtain orange-yellow BiOCl 0.7 I 0.3 , which is BOCI nanosheet.
[0085] Step 3, compound PCN and BOCI nanosheets by simple mixing method:
[0086] Weigh 0.9 g 0.5% PCN and 0.1 g BOCI nanosheets, add them into a beaker containing 40 mL ethanol, ultrasonicate them for 30 min at 60 KHz, stir for 8 h, dry the water in a water bath at 80 °C, collect the catalyst, and dry it again to obtain P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst (denoted as 9:10.5% PCN / BOCI).
[0087] Example 5
[0088] A P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalyst, the preparation steps are as follows:
[0089] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain precursor PCN:
[0090] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a 1% P:C3N4 molar ratio), dissolve them in 60mL of distilled water in a beaker, and dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed. Dry them in an oven at 80°C for 12 hours, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 3 hours. After natural cooling, take them out and grind them into powder to obtain blocky C3N4.
[0091] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 4°C / min, a target temperature of 550°C, and a holding time of 3h. The obtained sample was 1% PCN.
[0092] Step 2, using a hydrothermal method to obtain BOCI nanosheets:
[0093] 1) 1.580g Bi(NO3)3, 0.208g KCl and 0.199g KI were added to 60mL deionized water, and after ultrasonic dispersion, the pH was adjusted to 6 with sodium hydroxide solution, and stirring was continued for 30min. Then, the mixture solution was transferred to a 100mL polytetrafluoroethylene autoclave and placed in an oven for hydrothermal reaction at 150℃ for 26h. After cooling to room temperature, the crude sample was collected, washed with deionized water and ethanol, dried at 80℃ for 12h, and ground to obtain orange-yellow BiOCl 0.7 I 0.3 , which is BOCI nanosheet.
[0094] Step 3, compound PCN and BOCI nanosheets by simple mixing method:
[0095] Weigh 0.5g 1% PCN and 0.5g BOCI nanosheets, add them to a beaker containing 40mL ethanol, ultrasonicate them at 50KHz for 1.5h, stir for 4h, dry the water in a water bath at 80℃, collect the catalyst, and dry it again. 0.7 I 0.3 Heterojunction photocatalyst (denoted as 5:51% PCN / BOCI).
[0096] Example 6
[0097] In this embodiment, P-doped C3N4 and BiOCl 0.7 I 0.3 The preparation method of the heterojunction photocatalyst is the same as that of Example 1, except that 0.6 g 0.5% PCN and 0.4 g BOCI nanosheets in Example 1 are replaced with 0.7 g 0.5% PCN and 0.3 g BOCI nanosheets. 0.7 I 0.3 The heterojunction photocatalyst was recorded as 7:30.5% PCN / BOCI.
[0098] Example 7
[0099] In this embodiment, P-doped C3N4 and BiOCl 0.7 I 0.3 The preparation method of the heterojunction photocatalyst is the same as that of Example 1, except that 0.6 g 0.5% PCN and 0.4 g BOCI nanosheets in Example 1 are replaced with 0.8 g 0.5% PCN and 0.2 g BOCI nanosheets. 0.7 I 0.3 The heterojunction photocatalyst was recorded as 8:20.5% PCN / BOCI.
[0100] Performance Testing
[0101] (I) Morphology test
[0102] P-doped C3N4 and BiOCl prepared in Example 1 0.7 I 0.3 Taking heterojunction photocatalyst as an example, a scanning electron microscope test was performed on it, and the test results are as follows Figure 1 and Figure 2 As shown. Among them, Figure 1 P-doped C3N4 and BiOCl prepared in Example 1 0.7 I 0.3 SEM image of heterojunction photocatalyst at 100nm scale. Figure 2 P-doped C3N4 and BiOCl prepared in Example 1 0.7 I 0.3 HRTEM image of the heterojunction (a) and SEM image at 5 nm scale (b).
[0103] Depend on Figure 1 and Figure 2 The test results show that the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The 2D / 2D layered stacking structure of BOCI and PCN in the heterojunction indicates the successful construction of the PCN and BOCI van der Waals heterojunction. A clear boundary between PCN and BOCI can be observed in the HRTEM image, which indicates that the BOCI and PCN prepared by the preparation method of the present invention are successfully composited.
[0104] (ii) XRD test
[0105] The P-doped C3N4 and BiOCl prepared by the present invention 0.7 I 0.3 Taking the heterojunction as an example, XRD test was performed on it, and the test results are as follows Figure 3 (In the figure, 6:4PCN / BOCI represents Example 1, 5:5PCN / BOCI represents Example 5, 5:5PCN / BOCI represents Example 6, 8:2PCN / BOCI represents Example 7, and 9:1PCN / BOCI represents Example 4).
[0106] Depend on Figure 3The test results show that PCN exhibits two characteristic peaks, located at 13.0° and 27.6°, corresponding to the (100) and (001) crystal planes of PCN. In the XRD spectrum of BOCI, there are characteristic peaks of BiOCl (JCPDS No 21-0102) and BiOI (JCPDS No 21-0102). The peaks with the highest peak intensity at 26.0° and 33.5° correspond to the (101) and (102) crystal planes of BiOCl, respectively, and the peak with the highest peak intensity at 32.7° corresponds to the (110) crystal plane of BiOI. It can be observed that after compounding, among the characteristic peaks of the composite material, the characteristic peak corresponding to the (100) crystal plane of CN located near 13.0° disappears, but with the increase of the content of PCN compounding, the (600) characteristic peak of BOCI located near 11.9° gradually moves to a lower angle, so it may be due to the close peak position and degeneration. These phenomena indicate the successful construction of the PCN / BOCI heterojunction.
[0107] (III) Optical absorption and energy band position analysis
[0108] The P-doped C3N4 and BiOCl prepared by the present invention 0.7 I 0.3 Taking heterojunction photocatalyst as an example, the light absorption capacity of the catalyst was studied using UV-visible diffuse reflectance spectroscopy. Figure 4 shown.
[0109] Depend on Figure 4 The test results show that P-doped C3N4, BiOCl 0.7 I 0.3 The light absorption capacity between the heterojunction and the PCN is not much different. The absorption edge of PCN is 474nm, and the absorption edge of BOCI is 580nm. With the introduction of BOCI, the absorption edge of the heterojunction gradually redshifts, indicating that the introduction of BOCI can enhance the light absorption performance of the heterojunction. The band gap of the material is calculated using the Tauc-plot method, such as Figure 4 As shown in (b). The band gaps Eg of PCN and BOCI are 2.66 and 2.57 eV, respectively. In addition, according to the VB-XPS spectrum ( Figure 4 In (c), the valence band potentials (E VB ) are 1.53 and 1.42 eV respectively. CB =E VB -E g Calculate the conduction band potential of the material, and its conduction band potential is -1.13 and -1.15 eV respectively. The flat band potential obtained by Mott-Schottky test is as follows Figure 4As shown in (d), both PCN and BOCI exhibit the characteristics of n-type semiconductors, and their intersection points with the X-axis relative to the silver chloride standard electrode are -1.10 and -1.12 eV, respectively. After conversion to the hydrogen standard electrode potential, their conduction band potentials are -1.12 and -1.14 eV, respectively, which are consistent with the results calculated by combining VB-XPS spectra with UV-visible diffuse reflectance spectra, indicating the reliability of the data.
[0110] (IV) Degradation effect test
[0111] The present invention adds 50 mg of 6:40.5% PCN / BOCI of Example 1 to 100 mL of 10 mg / L potassium dichromate solution, 100 mL of 10 mg / L tetracycline hydrochloride solution, and 100 mL of 10 mg / L rhodamine B solution as degradation materials, and tests the degradation effect of the pollutants. The test results are as follows: Figure 5 shown.
[0112] Depend on Figure 5 The test results show that the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The heterojunction can effectively degrade pollutants such as Cr(VI), tetracycline hydrochloride and rhodamine B. In which, within 20 minutes, the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The degradation efficiency of tetracycline hydrochloride in 10 mg / L tetracycline hydrochloride aqueous solution of the heterojunction reached more than 70%. Within 20 minutes, the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The degradation efficiency of the heterojunction for Cr(VI) in 10 mg / L potassium dichromate aqueous solution was over 80%. Within 20 min, the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The degradation efficiency of the heterojunction for Rhodamine B in a 10 mg / L Rhodamine B aqueous solution reaches 100%, and the degradation effect is significant.
[0113] The present invention also uses 0.5% PC3N4 and BOCI in Example 1 as degradation agents, and takes 50 mg of the precursor 0.5% PC3N4 and BOCI prepared in Example 1 and places them in 100 mL of an aqueous solution containing 10 mg / L potassium dichromate and 100 mL of an aqueous solution containing 10 mg / L tetracycline hydrochloride to test the catalytic performance. The test results show that within 20 minutes, the degradation rates of 0.5% PC3N4 and BOCI prepared in Example 1 on Cr(VI) in a 10 mg / L potassium dichromate aqueous solution and tetracycline hydrochloride in a 10 mg / L tetracycline hydrochloride aqueous solution are 45% and 69%, respectively. It can be seen from the above test results that within 20 minutes, the P-doped C3N4 prepared in Example 1 and BiOCl 0.7 I 0.3 The degradation rates of Cr(VI) in 10 mg / L potassium dichromate aqueous solution and tetracycline hydrochloride in 10 mg / L tetracycline hydrochloride aqueous solution by heterojunction were 71% and 89%, respectively, which demonstrated the effectiveness of the heterojunction engineering modification strategy. The construction of heterojunction enhanced the light absorption ability of the catalyst and promoted the separation of photogenerated carriers. The enlarged specific surface area provided more active sites for the reaction. The Z-type charge transfer mechanism provided stronger reduction ability while promoting carrier separation.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A P-doped C3N4 and BiOCl 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The following steps are involved: After dissolving melamine and ammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN; After Bi(NO3)3, KCl and KI are uniformly dispersed in solvent 2, the pH is adjusted and then a hydrothermal reaction is performed to obtain BOCI nanosheets; The PCN and BOCI nanosheets are uniformly dispersed in solvent 3 and dried until solvent 3 is completely removed to obtain the P-doped C3N4 and BiOCl 0.7 I 0.3 Heterojunction photocatalysts.
2. P-doped C3N4 and BiOCl according to claim 1 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The solvent 1 is water; the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.1% to 3%.
3. P-doped C3N4 and BiOCl according to claim 1 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The two thermal condensation reactions are specifically as follows: firstly, the temperature is increased to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 2-3 hours. After the temperature is kept, the temperature is cooled to room temperature, the reaction product is ground, and then the ground powder is heated to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 3-4 hours.
4. P-doped C3N4 and BiOCl according to claim 1 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The solvent 2 is water, and the pH is 6; the mass ratio of Bi(NO3)3, KCl and KI is 395:52:
49.
5. P-doped C3N4 and BiOCl according to claim 1 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The temperature of the hydrothermal reaction is 150-160° C. and the time is 20-26 hours.
6. P-doped C3N4 and BiOCl according to claim 1 0.7 I 0.3 A method for preparing a heterojunction photocatalyst, characterized in that: The solvent 3 is ethanol; the mass ratio of the PCN to the BOCI nanosheets is 9:1 to 5:
5.
7. A P-doped C3N4 and BiOCl prepared by the preparation method according to any one of claims 1 to 6 0.7 I 0.3 Heterojunction photocatalysts.
8. A P-doped C3N4 and BiOCl as claimed in claim 7 0.7 I 0.3 Application of heterojunction photocatalyst in photocatalytic degradation of pollutants; the pollutants are Cr(VI), tetracycline hydrochloride or rhodamine B.